2016
DOI: 10.1016/j.dci.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow fat and the decline of B lymphopoiesis in rabbits

Abstract: B lymphopoiesis is necessary to generate a diverse pool of naïve B cells that are able to respond to a broad spectrum of antigens during immune responses to pathogens and to vaccination. Rabbits have been utilized for many years to generate high affinity monoclonal and polyclonal antibodies. Specific antibodies generated in rabbits have greatly advanced scientific discoveries, but the unique qualities of rabbit B cell development have been underappreciated. Unlike in humans and mice, where B lymphopoiesis decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 138 publications
(186 reference statements)
0
10
0
Order By: Relevance
“…Rabbit B lymphopoiesis declines at an accelerated rate compared to that of elderly humans and aged mice (29, 4956). In this study, we found that the arrest of B lymphopoiesis in young rabbits is associated with increased fat, myeloid cells, and inflammatory molecules, conditions similar to those seen in BM of aged humans and mice (4, 1015, 19, 21, 5759).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbit B lymphopoiesis declines at an accelerated rate compared to that of elderly humans and aged mice (29, 4956). In this study, we found that the arrest of B lymphopoiesis in young rabbits is associated with increased fat, myeloid cells, and inflammatory molecules, conditions similar to those seen in BM of aged humans and mice (4, 1015, 19, 21, 5759).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of inflammatory cytokines, including IL-1, IL-6, and TNFα, are found in aged BM, and all of these are known to negatively regulate B lymphopoiesis, and enhance myelopoiesis (22–28). We previously showed that adipocytes inhibit B lymphopoiesis in vitro , and that this inhibition is mediated in part, by IL-1 (23, 29). Adipocytes also express other inflammatory molecules, such as S100A8 and S100A9 (30, 31), and their expression is increased in multiple tissues during aging in mice and humans (32).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although MDSCs usually suppress proliferation of T cells by secreting inducible nitric oxide synthase (iNOS) and arginase, these mechanisms do not play a role in B lymphopoiesis [ 29 ]. Treatment with IL-1 also increases the number of CD11b + Gr1 + myeloid cells in culture by promoting myelopoiesis at the multipotent progenitor stage [ 29 , 32 ].…”
Section: Mdsc-mediated Regulation Of B Cell Differentiationmentioning
confidence: 99%
“…In the mouse retrovirus immunodeficiency system, ex vivo derived M-MDSCs from LP-BM5-infected mice also induced a moderate expansion of Tregs in vitro, but concurrently suppressed their IL-10 production (114 (44,162). More recent study showed that MDSCs in the bone marrow of aged mice suppressed B cell lymphopoiesis in an IL-1-dependent manner (74,75). B cells play crucial roles in cancer as sources of malignant cells in several lymphomas (136) and as sources of tumor-specific antibodies (144).…”
Section: Cd4mentioning
confidence: 99%